Konsep Dan Paradigma Mutu Pendidikan Dasar, Menengah dan Tinggi - Refnawati, Refnawati; Jamilus, Jamilus; Misrawani, Misrawani; Irawadi, Hermen (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the concept and paradigm of education quality at the primary, secondary, and tertiary levels. The approach used is library research with systematic searches through various databases such as Google Scholar, ERIC, ScienceDirect, SpringerLink, DOAJ, and the Garuda national repository. The literature analysed includes scientific books, reputable national and international journals, proceedings, and policy documents published between 2000 and 2025. The selection process was carried out by considering the relevance to the theme of quality and educational paradigms, as well as the availability of full texts in Indonesian or English. Data analysis was conducted qualitatively using content analysis techniques. The results of the study show that a culture of quality is a foundation of values that creates an environment conducive to continuous quality improvement, especially in the context of Islamic education based on Islamic values. In addition, the competitiveness of higher education institutions is determined by their ability to maintain excellence through quality improvement, innovation, and services that meet the needs of the world of work. This competitiveness is strengthened by the quality of human resources, educational programmes, technology, governance, and a culture of quality that is consistently developed. Thus, strengthening quality, establishing a culture of quality, and increasing competitiveness are strategic elements in ensuring the sustainability of educational institutions amid global dynamics and the ever-evolving needs of society.